Analytical Study of Applying the Energy Efficiency Design Index (EEDI) On an Existing Ship - حاتم, وهاد (Latakia University Journal -Engineering Sciences Series, 2022)
The International Maritime Organization (IMO) has adopted a new regulation to prevent air pollution from ship emissions which concentrated on reducing green gas emissions from shipping for existing ships, and energy efficiency measures for the new ship. This new regulation imposes a measure which is called Energy Efficiency Design Index (EEDI). This new measure aims to reduce CO2emissions and global environmental pollution by using fewer fossil fuels and less greenhouse gas emissions. EEDI is an implementation for all new ships larger than 400 GT. In this paper, one of the container ships of the Turkish maritime trade fleet was analyzed in terms of energy efficiency performance. The ship`s energy efficiency was found as an energy-efficient. Some practical proposals have been presented to improve ship`s energy efficiency in the short, medium and long term. This study is the first one which focused on one of the container ship energy efficiency. For Exempel, a plan called the Ship Energy Efficiency Management Plan (SEEMP) had been developed, and become mandatory for all vessels with GRT > = 400, This plan includes a set of actions to improve the ship's energy efficiency, such as planed maintenance of machinery and equipment. Operational management of Steam Boiler onboard the ship, regulate the operation of the generators so that the unnecessary generator is stopped in a timely manner, cleaning the hull of the ship of the fouling, cleaning the propeller, suitable immersion for the propeller, The suitable trim of the ship, choosing the most suitable navigational route, as well as behavioral procedures such as not lighting unoccupied spaces if not necessary and managing the operation of air conditioners and isolating accommodation rooms well... etc